Recent advancements in NIR spectroscopy for assessing the quality and safety of horticultural products: A comprehensive review - Pandiselvam, R.; Prithviraj, V.; Manikantan, M. R.; Kothakota, Anjineyulu; Rusu, Alexandru Vasile; Trif, Monica; Mousavi Khaneghah, Amin (Frontiers in Nutrition, 2022)
The qualitative and quantitative evaluation of agriculture products has been carried out using traditional destructive techniques. Due to their inherent disadvantages, the non-destructive methods using NIR spectroscopy coupled with chemometrics could be useful to evaluate various agriculture products. The advancement in computational power, machine learning, regression models, artificial neural network (ANN), and other predictive tools had made their way into NIRS, improving its potential to be a feasible alternative to destructive measurements. Nevertheless, the incorporation of suitable preprocessing and wavelength selection was found to have arguably proven its practical feasibility. The current review focuses on various computation methods used for processing the spectral data collected and the potential application of NIRS in the quality and safety evaluation of agriculture products was discussed. Additionally, the associated challenges and future perspectives of this technology are highlighted. NIRS is a potential tool for the rapid assessment of agriculture product quality and safety.